Respiratory Syncytial Virus-Associated Hospitalizations in Children: A 10-Year Population-Based Analysis in Finland, 2008–2018 - Uusitupa, Erika (American Academy of Pediatrics, 2025)
Background: The risk of respiratory syncytial virus (RSV) hospitalization is highest during the first months of life, but few studies have assessed the population-based rates of hospitalization in monthly age groups of infants.
Methods: We determined the average population-based rates of hospitalization with virologically confirmed RSV infections in children ≤15 years of age admitted during the 10-year period of 2008-2018. Testing for RSV was routine in all children hospitalized with respiratory infections, and all RSV-positive children admitted at any time during the study period were included in the analyses.
Results: The annual population-based rate of RSV hospitalization was highest in infants 1 month of age (52.0 per 1000 children; 95% CI, 45.2-59.7), followed by infants <1 month of age (34.8 per 1000; 95% CI, 29.2-41.1) and those 2 months of age (32.2 per 1000; 95% CI, 26.9-38.4). In cumulative age groups, the rate of hospitalization was 39.7 per 1000 (95% CI, 36.2-43.4) among infants <3 months of age, 26.8 per 1000 (95% CI, 24.8-29.0) in infants aged <6 months, and 15.8 per 1000 (95% CI, 14.7-17.0) in those <12 months of age.
Conclusion: In monthly age groups of infants, the incidence rates of virologically confirmed RSV hospitalization in all infants up to 3 months of age were substantially higher than those reported in earlier studies. These data may be important for improving the estimates of the cost-effectiveness of various interventions to reduce the burden of RSV in young infants.